Materiais de adorno visigótico de Patalou-Nisa - Arezes, Andreia (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This article aims to define the cultural context of a set of Visigothic metallic elements recovered from Patalou. Patalou is a site located in the county of Nisa, but it has not as yet been excavated. The artefacts of adornment, produced in bronze, and used over costume, are: three pieces of belt buckles, a simple buckle and an isolated component of a buckle. The analysis and interpretation developed in this text attempt to sort the artefacts according to a typology, in order to discuss their artistic, political, religious and chronological context. In doing so, I will compare the artefacts to those from well known Visigoth sites, namely burial sites located in the Iberian Peninsula.